Oral Teachings of Old Women in 1 Timothy 4:7 - Torbus, Sławomir (2019)
The paper attempts to consider the possibility that the expression γραώδεις μῦθοι used in 1 Timothy 4:7 might refer to oral teachings conveyed by older women in Ephesus. It can be observed that in the Pastoral Epistles, the word μῦθοι denotes false teachings which stand in sharp contrast with the truth contained in the written Scriptures. The context of 1 Timothy may suggest the possibility that older women could convey such oral teachings in the space of the οἶκος, which was a natural ecclesiastical environment of the earliest Christian church.
Keywords: Pastoral Epistles; myth; New Testament; orality; Paul of Tarsus; early Christianity